Characterization of Turn-On Time Delay in a Fiber Grating Fabry–Perot Lasers - Hisham, H.K.; Mahdiraji, Ghafour Amouzad; Abas, A.F.; Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd (Institute of Electrical and Electronics Engineers (IEEE), 2012)
In this paper, turn-on time delay characteristics of a fiber grating Fabry-Perot (FGFP) laser are numerically investigated by considering all the carrier recombination rate (CRR) R(N) coefficients (nonradiative, A(nr); radiative, B; and Auger coefficient, C). The results show that the turn-on time delay significantly reduces by increasing the injection current (I-inj) and/or the initial value of carrier density (N-i). Meanwhile, the turn-on time delay increases by increasing the CRR coefficients. However, its effect can be minimized by increasing I-inj and/or N-i. In addition, the turn-on time delay can be reduced by increasing the external optical feedback (OFB) level. Moreover, it is shown that the optimum external-cavity length (L-ext) is 3.1 cm. Furthermore, an antireflection (AR) coating reflectivity value of 1 X 10(-2) is sufficient for the laser to operate at good turn-on time delay and low fabrication complexity. The obtained results can provide an important idea for the practical fabrication of the FGFP laser used in the dense wavelength-division multiplexing (DWDM) systems and optical access networks.